Efficacy and Safety Outcome Comparison of Endoresection and Proton Beam Therapy as Primary Treatment for Choroidal Melanoma - Denisa Anggi Kurnia; Neni Anggraini (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2020)
Objective: To evaluate and compare the efficacy and safety between endoresection and proton beam radiotherapy, as primary treatment in choroidal melanoma.Methods: Articles that were published from 2008 to 2018 were collected from multiple sources including Pubmed, Clinical Key, and Ophthalmology Advance. All study that comply with the inclusion and exclusion criteria were categorized based on level of evidence Oxford Center for Evidence-based Medicine Levels of Evidence. Primary outcome is secondary enucleation. Secondary outcomes are metastasis, recurrence, death, visual outcomes, and complication. Result: Twelve articles were eligible to be reviewed. Mean secondary enucleation, metastasis, and death rate is lower in endoresection group (6.29% vs 12.94%; 8.00% vs 20.85%; 6.86% vs 20.43) while recurrence rate is lower in proton beam group (4.78% vs 6.86%). The most common complication that observed is retinal detachment. Other complications that were reported includes cataract formation, radiation retinopathy, neovascular glaucoma, vitreous hemorrhage, elevated intraocular pressure (IOP), iris neovascularization, and optic neuropathy. Conclusion: Endoresection as primary treatment for choroidal melanoma shows better efficacy compared to proton beam therapy, regarding the ability to preserve the eyeball. The safety between endoresection and proton beam therapy, both therapy shows similar result.